2012
DOI: 10.1063/1.4759505
|View full text |Cite
|
Sign up to set email alerts
|

Structures and magnetism of multinuclear vanadium-pentacene sandwich clusters and their 1D molecular wires

Abstract: Two types of multinuclear sandwich clusters, (V(3))(n)Pen(n+1), (V(4))(n)Pen(n+1) (Pen = Pentacene; n = 1, 2), and their corresponding infinite one-dimensional (1D) molecular wires ([V(3)Pen](∞), [V(4)Pen](∞)) are investigated theoretically, especially on their magnetic coupling mechanism. These sandwich clusters and molecular wires are found to be of high stability and exhibit intriguing magnetic properties. The intra-layered V atoms in (V(3))(n)Pen(n+1) clusters prefer antiferromagnetic (AFM) coupling, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…Ant] ∞ SMWs, the TMs are distanced from the mass center of their facing hexagonal ring in the Ant ligands (d TM-Ant ) by around 1.84-2.27 Å and 1.86-2.19 Å, respectively. On one hand, our results are close to previous reported TM-PHM complexes [38,40,41]. On the other hand, the TM-ligand distances are a bit larger than those in MHM sandwich complexes [8-10, 12, 13] due to their direct TM-TM coupling.…”
Section: Computation Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…Ant] ∞ SMWs, the TMs are distanced from the mass center of their facing hexagonal ring in the Ant ligands (d TM-Ant ) by around 1.84-2.27 Å and 1.86-2.19 Å, respectively. On one hand, our results are close to previous reported TM-PHM complexes [38,40,41]. On the other hand, the TM-ligand distances are a bit larger than those in MHM sandwich complexes [8-10, 12, 13] due to their direct TM-TM coupling.…”
Section: Computation Methodssupporting
confidence: 89%
“…Similarly, the magnetic ordering in these PHM sandwich compounds can be effectively modulated by doping hetero metal atoms or organic ligands [40]. Compared with MHM sandwich complexes, the origin of the magnetic ordering in such PHM sandwich compounds are much more complicated, multiple magnetic exchange interactions, such as super exchange and direct exchange interactions, were revealed to be coexist and compete with each other [29,41]. However, people's efforts on these PHM sandwich complexes are rather scarce, particularly, some common concerns such as the magnetic stability, the spin based transport behaviors, and so forth have not been extended yet.…”
mentioning
confidence: 99%
“…O'Hare and coworkers and Ashley et al fabricated the permethylpentalene (Pn* = C 8 Me 6 ), Pn* 2 M 2 (M =Li, V, Cr, Mn, Co, Ni) clusters . Many other polycyclic hydrocarbon molecules have been used to form PHPSs, such as cycloheptatrienyl, naphthalene heptallene, cyclooctatetraene, anthracene (= Ant = C 14 H 10 ), pyrene, tetracene, and pentacene (= Pen = C 22 H 14 ), and so on.…”
Section: Polycyclic Hydrocarbon‐polymetal Sandwich Complexesmentioning
confidence: 99%
“…Besides, PHPSs with a larger polycyclic‐hydrocarbon‐ligand have been investigated as well. Very interestingly, the competition between indirect superexchange and direct exchange interactions in such can result in different magnetic coupling . For example, magnetic calculations of V 2 n Ant n + 1 clusters showed that for n ≤ 2, the intralayered vanadium atoms are AFM coupling, but for n ≥ 3, they favor FM coupling.…”
Section: Polycyclic Hydrocarbon‐polymetal Sandwich Complexesmentioning
confidence: 99%
“…[1][2][3] Considerable theoretical interest has also been paid to organometallic sandwich nanowires, [M x (L)] N , as models for molecular ferromagnets and spintronic devices. [4][5][6][7] The aromatic pentalene dianion, [C 8 H 6 ] 2À = Pn, displays a unique variety of coordination modes in its organometallic complexes. 8 In particular its ability to coordinate two metals in a syn-facial manner has proved ideal for the synthesis of such doublesandwich complexes.…”
mentioning
confidence: 99%